La química cuántica y el premio nobel 1998 - López Castañares, Rafael; Rojas Pedral, Mercedes; Olea Cardoso, Óscar (CIENCIA ergo-sum; Vol. 6 Núm. 2 (1999): CIENCIA ergo-sum (julio-octubre 1999), 2017)
-